Comparison of Ti(C, N)-based cermets by vacuum and gas-pressure sintering: Microstructure and mechanical properties. Issue 1 (January 2018) - Xiong, Huiwen; Wu, Yuxue; Li, Zhiyou; Gan, Xueping; Zhou, Kechao; Chai, Liyuan
Abstract: Ti(C, N)-based cermets with different carbon content were prepared by vacuum sintering and gas pressure sintering (Ar, 20 MPa). Effects of carbon content and sintering method on the microstructure, composition and mechanical properties of cermets were studied. Results showed average grain size and thickness of rim phase to increase with higher carbon or by gas pressure sintering, which was caused by the accelerated dissolution-precipitation process. More uniform morphology with broadened grain size distribution was obtained by gas pressure sintering, leading to improved density and properties. Cermets with 0.8 wt%C showed the best mechanical properties, i.e. 2105 MPa (TRS), 10.55 MPa m 1/2 (KIC ), and 1581 (HV 10), although containing residue Ni2 (W, Ti)4 C. Further increasing the carbon addition leads to thick rims and high amount of white core-grey rim phases, which can deteriorate the properties. Adequate control of size and composition of the core-rim structure plays a key role in ensuring satisfactory mechanical properties.